Anthropogenic geoasset exploration in Bukit Besi for geotourism development: a preliminary study - Marilah Sarman; Nor Shahidah Mohd Nazer; Kadderi Md Desa; Azimah Husin; Norasiah Sulaiman; Amir Huzairy (Penerbit Universiti Kebangsaan Malaysia, 2019)
Geotourism is a responsible and sustainable type of tourism package development, equivalent to ecotourism, and other nature-based derivatives of tourism with deeper level considerations on local landscapes and the underlying geological foundation. The area was investigated from the perspective of tourism geoscience sub-discipline with a focus on non-extractive natural resources. Taking into consideration the beach alluvial plain, human community, the biophysical components and the mining artifacts, mineralization, geological formation, mining history and people lifestyle during the active mining period. Bukit Besi’s rail transit system as example, with eleven stations, used to transport people, goods and ores between Bukit Besi and a coastal town of Dungun. Geology of Bukit Besi consist of dominance of shale, quartzite, limestone; intrusion rocks of granite and quartz vein, and metasediment rock. Iron mineralization occurs as a result of replacement in shale, limestone, granite and along the developed fractures. Further study relates the interconnection between iron mineralization and cultural of the residents. Mineralization had created the mining operation in Bukit Besi. History of mining process, life of Bukit Besi residents and railway is part of intrinsic information that make higher value of monument left in Bukit Besi in tourism context. Historical narration of the mining region goes beyond events related to human time frame but spans the geological history of the regions and the story of interactions between human and their environments. These form the basis for the creation of anthrobiogeoasset for regional planning of the region. Secondary utilization of the non-extractive natural resource should incorporate tourism and business components for sustainable geotourism package development of Bukit Besi, Malaysia